Composite layer polyether-ether-ketone organic solvent nanofiltration membrane as well as preparation method and application thereof

By introducing PDA-ZIF-8 nanoparticles into the polyether ether ketone membrane to form a composite nanofiltration membrane, the chemical stability problem of the existing membrane under high temperature and harsh working conditions is solved, and a variety of solvent systems are realized The efficient separation performance and stability in the process have expanded the scope of application.

CN119281134AActive Publication Date: 2025-01-10WUHAN ZHSB ENVIRONMENTAL TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411665513.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-01-10
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

The existing organic solvent nanofiltration membrane has weak chemical stability under high temperature and harsh working conditions, making it difficult to maintain performance in highly corrosive and highly oxidative solvents, and it is difficult to regulate permeability.

Method used

The composite layer polyether ether ketone film is used to form a selective separation layer by sulfonated polyether ether ketone based film as a support layer, and PDA-ZIF-8 nanoparticles are polymerized at its interface to form a selective separation layer to improve the solvent resistance and stability of the film.

Benefits of technology

It achieves efficient separation performance in different polar protons, polar aprotons and non-polar solvent systems, and maintains the membrane structure intact under high temperature conditions, making it suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119281134A_ABST
    Figure CN119281134A_ABST
Patent Text Reader

Abstract

The invention provides a composite layer polyether-ether-ketone organic solvent nanofiltration membrane. The nanofiltration membrane comprises a supporting layer and a selective separation layer, the support layer is a sulfonated polyetheretherketone base membrane, and the selective separation layer is a polyamide film formed by polymerizing piperazine monomers, PDA-ZIF-8 nanoparticles and acyl chloride monomers on the interface of the support layer. According to the invention, polydopamine (PDA) is adopted to carry out coating modification on ZIF-8, so that the dispersibility of ZIF-8 in water is improved, and the non-selective defect caused by non-uniform dispersion of nanoparticles is avoided; furthermore, a sulfonated polyetheretherketone membrane base membrane is adopted as a supporting layer, superfine PDA-ZIF-8 nanoparticles are introduced into a polyamide selective separation layer through an interfacial polymerization process, and the prepared organic solvent nanofiltration membrane has excellent solvent resistance and high temperature resistance and is wide in industrial application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of membrane separation, and in particular relates to a composite-layer polyetheretherketone organic solvent nanofiltration membrane and a preparation method and application thereof. Background Art

[0002] Membrane separation technology is a green separation technology that uses the screening properties of membrane materials to separate and purify target components. Compared with traditional separation technologies, membrane separation technology has the advantages of high efficiency, low energy consumption, and simple operation. Organic solvent nanofiltration (OSN) is an emerging membrane separation technology that separates organic solutions from target components by applying a pressure gradient on the feed side of the membrane to achieve concentration and recovery of target components. In recent years, it has been widely used in processes such as solvent-containing wastewater treatment, organic waste liquid recovery, biochemical synthesis and purification. At present, most organic solvent nanofiltration membranes are mainly made of polymers such as polyimide (PI) and polybenzimidazole (PBI). Through cross-linking post-treatment, these polymer membranes have good solvent resistance in most aprotic solvents, but their thermal stability and chemical stability under harsh working conditions are relatively weak, which greatly limits their promotion and application.

[0003] Polyetheretherketone (PEEK), a semi-crystalline polymer with a linear aromatic main chain structure, has attracted widespread attention due to its excellent heat resistance, chemical resistance and high mechanical strength. However, PEEK is only soluble in some strong proton acids at room temperature, and its excellent solvent resistance makes it more difficult to process into membranes. Peeva et al. first dissolved PEEK powder in methanesulfonic acid (MSA) and SA solutions at room temperature and prepared membranes by phase inversion. The results showed that the PEEK membrane prepared by the one-step method of MSA / SA solution did not require cross-linking, and could effectively separate N,N-dimethylformamide (DMF) solvent at a high temperature of 80°C, and the Pd catalyst retention recovery rate for long-term continuous Heck coupling reactions reached 93%. Da Silva Burgal et al. first used the PEEK membrane prepared by this method for organic solvent nanofiltration, and obtained nanofiltration performance by annealing at 20°C. After annealing, the permeation flux of PEEK membrane for tetrahydrofuran (THF) increased from 28L / (h·m 2 bar) to 0.22L / (h·m 2 bar), the molecular retention capacity was increased to 400~600g / mol. In addition, Da Silva Burgal also controlled the permeability separation of the membrane by changing the solvent type of the membrane pores before annealing, and the WMCO of the membrane varied from 295 to 1400 g / mol. The preparation method of dissolving PEEK in a sulfonic acid solvent and directly processing it into a membrane is simple and low-cost. The prepared PEEK membrane is not only resistant to high temperatures, but also can perform membrane separation in strong acids, strong bases and harsh organic solvents.

[0004] However, since an acidic solution is used as the coating solution to prepare the membrane, it is difficult to regulate the permeability of the PEEK membrane by adding additives such as pore formers and volatile co-solvents to this highly corrosive and highly oxidizing coating solution. Summary of the invention

[0005] In view of this, the present invention provides a composite-layer polyetheretherketone organic solvent nanofiltration membrane and a preparation method and application thereof.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions: A composite polyetheretherketone organic solvent nanofiltration membrane, the nanofiltration membrane comprising a support layer and a selective separation layer; the support layer is a sulfonated polyetheretherketone base membrane, and the selective separation layer is a polyamide film formed by polymerizing piperazine monomers, PDA-ZIF-8 nanoparticles, and acyl chloride monomers at the interface of the support layer; Wherein, the PDA-ZIF-8 nanoparticles are prepared by the following method: S11, preparing a zinc nitrate hexahydrate-methanol solution and a 2-methylimidazole-methanol solution, mixing, stirring, centrifuging, removing the supernatant, washing with methanol, and vacuum drying to obtain ZIF-8 nanosheets; S12. Disperse ZIF-8 nanosheets in methanol, add Tris buffer and dopamine hydrochloride, stir, centrifuge, remove the supernatant and wash with methanol, and vacuum dry to obtain PDA-ZIF-8 nanoparticles.

[0007] Furthermore, in step S11, the molar ratio of zinc nitrate hexahydrate to 2-methylimidazole is 1:(5-10), stirring is performed for 0.5-4 hours, the centrifugal speed is 6000-12000 rpm, methanol washing is repeated 2-5 times, and the vacuum drying temperature is 40-70°C.

[0008] In some specific embodiments, preferably, in step S11, the molar ratio of zinc nitrate hexahydrate to 2-methylimidazole is 1:8, stirring is performed for 1 hour, the centrifugal speed is 10000 rpm, methanol washing is repeated 3 times, and the vacuum drying temperature is 60°C.

[0009] Furthermore, in step S12, the mass ratio of ZIF-8 nanosheets to dopamine hydrochloride is (5-20):1, the concentration of Tris buffer is 10-30 mM, stirring is performed for 4-6 hours, the centrifugal speed is 6000-12000 rpm, methanol washing is repeated 2-5 times, and the vacuum drying temperature is 40-70°C.

[0010] In some specific embodiments, preferably, in step S12, the mass ratio of ZIF-8 nanosheets to dopamine hydrochloride is 10:1, the concentration of Tris buffer is 10 mM, stirring is 5 h, the centrifugal speed is 10000 rpm, methanol washing is repeated 3 times, and the vacuum drying temperature is 60°C.

[0011] Furthermore, the piperazine monomers include hexahydropyrazine, N-methylpiperazine, and N-ethylpiperazine; and the acyl chloride monomers include trimesoyl chloride.

[0012] In some specific embodiments, preferably, the piperazine monomer is hexahydropyrazine; and the acyl chloride monomer is trimesoyl chloride.

[0013] A method for preparing the above-mentioned nanofiltration membrane comprises the following steps: S21, dissolving polyetheretherketone in a mixed solution of methanesulfonic acid and sulfuric acid, stirring, and standing to remove bubbles to obtain a casting solution; coating the casting solution on a non-woven fabric support, standing, and immersing it in a deionized water precipitation bath to phase transform into a membrane, and washing the membrane to obtain a sulfonated polyetheretherketone base membrane; S22, dispersing PDA-ZIF-8 nanoparticles in a piperazine monomer solution to prepare an aqueous phase solution, and dissolving an acyl chloride monomer in a normal hexane solution to prepare an organic phase solution; S23, pouring the aqueous solution in step S22 onto the surface of the base membrane and letting it stand, and removing the excess aqueous solution on the membrane surface with a rubber roller; then slowly pouring the organic solution in step S22 onto the membrane surface, reacting, drying, and baking to obtain a nanofiltration membrane.

[0014] Furthermore, in step S21, the content of polyetheretherketone in the sulfonated polyetheretherketone-based membrane is 5-20wt%; and the molar ratio of methanesulfonic acid to sulfuric acid is (1-5):1.

[0015] In some specific embodiments, preferably, in step S21, the content of polyetheretherketone in the sulfonated polyetheretherketone-based membrane is 12 wt %; and the molar ratio of methanesulfonic acid to sulfuric acid is 2.5:1.

[0016] Furthermore, in step S22, the concentration of piperazine monomers in the aqueous solution is 0.0025-1.5 wt %; and the concentration of PDA-ZIF-8 nanoparticles in the aqueous solution is 0.001-0.02 wt %.

[0017] In some specific embodiments, preferably, the concentration of piperazine monomers in the aqueous solution of step S22 is 0.3 wt %, and the concentration of PDA-ZIF-8 nanoparticles in the aqueous solution is 0.012 wt %.

[0018] Furthermore, the concentration of the acyl chloride monomer in the organic phase solution in step S22 is 0.001-1.0 wt %.

[0019] In some specific embodiments, preferably, the concentration of the acyl chloride monomer in the organic phase solution in step S22 is 0.2 wt %.

[0020] Furthermore, in step S23, the aqueous solution is allowed to stand on the base film for 0.5 to 5 minutes, and the organic solution is allowed to react on the base film for 0.5 to 2 minutes; the baking conditions are: 40 to 70° C., 5 to 30 minutes.

[0021] In some specific embodiments, preferably, in step S23, the aqueous solution is allowed to stand on the base film for 2 minutes, and the organic solution is allowed to react on the base film for 1 minute; the baking conditions are: 60° C., 15 minutes.

[0022] Application of the above nanofiltration membrane in separation of organic solution systems.

[0023] Compared with the prior art, the present invention has the following beneficial effects: The present invention uses polydopamine (PDA) to coat and modify ZIF-8, and utilizes a large number of active groups such as phenolic hydroxyl groups and amino groups contained in polydopamine. These functional groups are linked to the outer wall of ZIF-8, which greatly improves the dispersibility of ZIF-8 in water and avoids the non-selective defects caused by uneven dispersion of nanoparticles; further, sulfonated polyetheretherketone membrane base membrane is used as a supporting layer, and ultrafine PDA-ZIF-8 nanoparticles are introduced into the polyamide selective separation layer through a simple process and highly repeatable interfacial polymerization process. The prepared organic solvent nanofiltration membrane has excellent solvent resistance. It can be used in different polar protons, polar aprotic solvents and non-polar solvent systems, and can also maintain a complete membrane structure for organic solvents under high temperature (80°C) conditions, and has broad industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is the SEM image of the PDA-ZIF-8 nanoparticles prepared in the present invention.

[0025] Figure 2 This is a SEM image of the sulfonated polyetheretherketone based membrane prepared in the present invention.

[0026] Figure 3 This is the SEM image of the nanofiltration membrane prepared in Comparative Example 1.

[0027] Figure 4 This is a SEM image of the polyetheretherketone organic solvent nanofiltration membrane containing PDA-ZIF-8 nanoparticles prepared in the present invention. DETAILED DESCRIPTION

[0028] The present invention is further described in detail below in conjunction with specific embodiments so that those skilled in the art can understand the present invention more clearly.

[0029] Example 1 This embodiment provides a composite layer polyetheretherketone organic solvent nanofiltration membrane, and the specific preparation method is as follows: Preparation of PDA-ZIF-8 nanoparticles: Prepare zinc nitrate hexahydrate-methanol solution and 2-methylimidazole-methanol solution, mix them according to the molar ratio of zinc nitrate hexahydrate to 2-methylimidazole 1:8, stir magnetically at room temperature for 1 hour, centrifuge at 10000 rpm for 10 minutes, remove the supernatant and wash repeatedly with methanol for 3 times, and vacuum dry at 60°C to obtain ZIF-8 nanosheets.

[0030] The ZIF-8 nanosheets obtained in the previous step were added to methanol and ultrasonically treated for 2 h to disperse evenly. Then, 10 mM Tris buffer and dopamine hydrochloride (the mass ratio of ZIF-8 nanosheets to dopamine hydrochloride was 10:1) were added, stirred at room temperature for 5 h, centrifuged at 10,000 rpm for 10 min, the supernatant was removed and washed with methanol for 3 times, and vacuum dried at 60 °C to obtain PDA-ZIF-8 nanoparticles.

[0031] Preparation of sulfonated polyetheretherketone based membrane: Dissolve polyetheretherketone in a mixed solution of methanesulfonic acid and sulfuric acid, stir and mix evenly, and let stand for 90 hours to remove bubbles to obtain a casting solution. The polyetheretherketone content in the casting solution is 12wt%, and the molar ratio of methanesulfonic acid to sulfuric acid is 2.5:1.

[0032] Using a blade scraper with a thickness of 200 μm, pour the casting liquid under the scraper, and apply the casting liquid to the non-woven fabric support at a lateral speed of 0.5 cm / s. After standing for 0.5 min, immerse it in a deionized water precipitation bath for phase transformation into a membrane. Change the water in the middle to keep the precipitation bath neutral, and clean the excess residual reagents in the sulfonated polyetheretherketone base membrane to obtain the sulfonated polyetheretherketone base membrane.

[0033] Preparation of polyetheretherketone organic solvent nanofiltration membrane containing PDA-ZIF-8 nanoparticles: The prepared PDA-ZIF-8 nanoparticles were dispersed in a hexahydropyrazine monomer solution and ultrasonically treated for 2 hours to obtain an aqueous phase solution, and trimesoyl chloride (TMC) was dissolved in a n-hexane solution to obtain an organic phase solution. The content of PDA-ZIF-8 nanoparticles in the aqueous phase solution was 0.003wt%, the content of hexahydropyrazine monomer in the aqueous phase solution was 0.3wt%, and the content of trimesoyl chloride in the organic phase solution was 0.2wt%.

[0034] The aqueous solution prepared above was poured onto the surface of the sulfonated polyetheretherketone base membrane and allowed to stand for 2 minutes, and the excess aqueous solution on the membrane surface was removed with a rubber roller; then the organic solution prepared above was slowly poured onto the membrane surface, reacted for 1 minute, dried for 2 minutes, and then placed in an oven for annealing at 60°C for 15 minutes to obtain a nanofiltration membrane.

[0035] Example 2 This embodiment provides a composite layer polyetheretherketone organic solvent nanofiltration membrane, and the specific preparation method is basically the same as that of Example 1, except that: the content of PDA-ZIF-8 nanoparticles in the aqueous phase solution is 0.006wt%, and the rest remains unchanged.

[0036] Example 3 This embodiment provides a composite layer polyetheretherketone organic solvent nanofiltration membrane, and the specific preparation method is basically the same as that of Example 1, except that: the content of PDA-ZIF-8 nanoparticles in the aqueous phase solution is 0.012wt%, and the rest remains unchanged.

[0037] Example 4 This embodiment provides a composite layer polyetheretherketone organic solvent nanofiltration membrane, and the specific preparation method is basically the same as that of Example 1, except that: the content of PDA-ZIF-8 nanoparticles in the aqueous phase solution is 0.036wt%, and the rest remains unchanged.

[0038] Example 5 This embodiment provides a composite layer polyetheretherketone organic solvent nanofiltration membrane, and the specific preparation method is as follows: Preparation of PDA-ZIF-8 nanoparticles: Zinc nitrate hexahydrate-methanol solution and 2-methylimidazole-methanol solution were prepared and mixed in a molar ratio of zinc nitrate hexahydrate to 2-methylimidazole of 1:5, magnetically stirred at room temperature for 1 hour, centrifuged at 6000 rpm for 15 minutes, the supernatant was removed and washed with methanol for three times, and vacuum dried at 40°C to obtain ZIF-8 nanosheets.

[0039] The ZIF-8 nanosheets obtained in the previous step were added to methanol and ultrasonically treated for 2 h to disperse evenly. Then, 20 mM Tris buffer and dopamine hydrochloride (the mass ratio of ZIF-8 nanosheets to dopamine hydrochloride was 5:1) were added, stirred at room temperature for 4 h, centrifuged at 6000 rpm for 15 min, the supernatant was removed and washed with methanol for 3 times, and vacuum dried at 40 °C to obtain PDA-ZIF-8 nanoparticles.

[0040] Preparation of sulfonated polyetheretherketone based membrane: Dissolve polyetheretherketone in a mixed solution of methanesulfonic acid and sulfuric acid, stir and mix evenly, and let stand for 90 hours to remove bubbles to obtain a casting solution. The polyetheretherketone content in the casting solution is 5wt%, and the molar ratio of methanesulfonic acid to sulfuric acid is 1:1.

[0041] Using a blade scraper with a thickness of 200 μm, pour the casting liquid under the scraper, and apply the casting liquid to the non-woven fabric support at a lateral speed of 0.5 cm / s. After standing for 2 minutes, immerse it in a deionized water precipitation bath for phase transformation into a membrane. Change the water in the middle to keep the precipitation bath neutral, and clean the excess residual reagents in the sulfonated polyetheretherketone base membrane to obtain the sulfonated polyetheretherketone base membrane.

[0042] Preparation of polyetheretherketone organic solvent nanofiltration membrane containing PDA-ZIF-8 nanoparticles: The prepared PDA-ZIF-8 nanoparticles were dispersed in an N-methylpiperazine solution and ultrasonically treated for 2 hours to obtain an aqueous phase solution, and trimesoyl chloride (TMC) was dissolved in a n-hexane solution to obtain an organic phase solution. The content of PDA-ZIF-8 nanoparticles in the aqueous phase solution was 0.012wt%, and the content of N-methylpiperazine monomer was 0.05wt%; the content of trimesoyl chloride in the organic phase solution was 0.01wt%.

[0043] The aqueous solution prepared above was poured onto the surface of the sulfonated polyetheretherketone base membrane and allowed to stand for 2 minutes, and the excess aqueous solution on the membrane surface was removed with a rubber roller; then the organic solution prepared above was slowly poured onto the membrane surface, reacted for 2 minutes, dried, and then placed in an oven for annealing at 40°C for 25 minutes to obtain a nanofiltration membrane.

[0044] Example 6 This embodiment provides a composite layer polyetheretherketone organic solvent nanofiltration membrane, and the specific preparation method is as follows: Preparation of PDA-ZIF-8 nanoparticles: Zinc nitrate hexahydrate-methanol solution and 2-methylimidazole-methanol solution were prepared and mixed in a molar ratio of zinc nitrate hexahydrate to 2-methylimidazole of 1:10, magnetically stirred at room temperature for 1 hour, centrifuged at 12000 rpm for 10 minutes, the supernatant was removed and washed with methanol for three times, and vacuum dried at 70°C to obtain ZIF-8 nanosheets.

[0045] The ZIF-8 nanosheets obtained in the previous step were added to methanol and ultrasonically treated for 2 h to disperse evenly. Then, 30 mM Tris buffer and dopamine hydrochloride (the mass ratio of ZIF-8 nanosheets to dopamine hydrochloride was 20:1) were added. The mixture was stirred at room temperature for 6 h, centrifuged at 12,000 rpm for 10 min, the supernatant was removed and washed with methanol for 3 times. The mixture was vacuum dried at 70 °C to obtain PDA-ZIF-8 nanoparticles.

[0046] Preparation of sulfonated polyetheretherketone based membrane: Dissolve polyetheretherketone in a mixed solution of methanesulfonic acid and sulfuric acid, stir and mix evenly, and let stand for 90 hours to remove bubbles to obtain a casting solution. The polyetheretherketone content in the casting solution is 20wt%, and the molar ratio of methanesulfonic acid to sulfuric acid is 5:1.

[0047] Using a blade scraper with a thickness of 200 μm, pour the casting liquid under the scraper, and apply the casting liquid to the non-woven fabric support at a lateral speed of 0.5 cm / s. After standing for 0.5 min, immerse it in a deionized water precipitation bath for phase transformation into a membrane. Change the water in the middle to keep the precipitation bath neutral, and clean the excess residual reagents in the sulfonated polyetheretherketone base membrane to obtain the sulfonated polyetheretherketone base membrane.

[0048] Preparation of polyetheretherketone organic solvent nanofiltration membrane containing PDA-ZIF-8 nanoparticles: The prepared PDA-ZIF-8 nanoparticles were dispersed in an N-ethylpiperazine solution and ultrasonically treated for 2 hours to obtain an aqueous phase solution, and trimesoyl chloride was dissolved in a n-hexane solution to obtain an organic phase solution. The content of PDA-ZIF-8 nanoparticles in the aqueous phase solution was 0.012wt%, and the content of N-ethylpiperazine monomer was 1.5wt%; the content of trimesoyl chloride in the organic phase solution was 1.0wt%.

[0049] The aqueous solution prepared above was poured onto the surface of the sulfonated polyetheretherketone base membrane and allowed to stand for 2 minutes, and the excess aqueous solution on the membrane surface was removed with a rubber roller; then the organic solution prepared above was slowly poured onto the membrane surface, reacted for 1 minute, dried for 2 minutes, and then placed in an oven for annealing at 60°C for 15 minutes to obtain a nanofiltration membrane.

[0050] Comparative Example 1 This comparative example provides a nanofiltration membrane, and the specific preparation method is basically the same as that of Example 1, except that: the aqueous phase solution does not contain PDA-ZIF-8 nanoparticles, and the rest remains unchanged.

[0051] Comparative Example 2 This comparative example provides a nanofiltration membrane, and the specific preparation method is basically the same as that in Example 1, except that the base membrane is prepared from commercial polysulfone with a molecular weight cutoff of 20,000 Da (purchased from Guochu Technology (Xiamen) Co., Ltd.), and the rest remains unchanged.

[0052] Furthermore, in order to understand the performance of the nanofiltration membranes prepared in the above embodiments and comparative examples, the following tests were also performed: Separation performance under different solution systems: At 25°C and a transmembrane pressure difference of 3.0 MPa, a cross-flow filtration device was used to test the separation performance of the membrane in different solution systems, and the final separation performance results are shown in Table 1. The solution system details are: 1000 mg / L sodium sulfate solution-water solution, 50 mg / L rhodamine B (positive charge, Mw=479.02 Da)-ethanol solution, 50 mg / L bengal (negative charge, Mw=1017.64 Da)-ethanol solution, 50 mg / L rhodamine B (positive charge, Mw=479.02 Da)-dimethylformamide solution.

[0053] Table 1 Separation performance of various nanofiltration membranes in different solution systems

[0054] It can be seen from the above table: The nanofiltration membranes prepared in Examples 1-6 reacted with sodium sulfate solution-water solution to form a sodium 2 SO 4 The interception rate of Rhodamine B in the Rhodamine B-ethanol solution system is 95.9-99.6%, the interception rate of Rhodamine B in the Rhodamine B-ethanol solution system is 93.1-98.3%, the interception rate of Bengal in the Bengal Red-ethanol solution system is 98.4-99.8%, and the interception rate of Rhodamine B in the Rhodamine B-dimethylformamide solution system is 90.1-98.0%. The nanofiltration membranes prepared in Examples 1-6 have good interception rates for solutes in different systems. Among them, by comparison, it can be seen that the interception rate shows a trend of first rising and then falling with the increase of the PDA-ZIF-8 nanoparticle dosage, and the interception rate is the largest when the dosage is 0.012wt%.

[0055] By comparing with Comparative Example 1, it was found that bengalensis had a good retention rate under each nanofiltration membrane because of its large molecular weight. When it was replaced with rhodamine B with a smaller molecular weight, the retention rate in Comparative Example 1 decreased significantly.

[0056] Permeation flux performance of different solvents: Under the conditions of 25°C and a transmembrane pressure difference of 3.0 MPa, the permeation flux of the membrane for different solvents was tested using a cross-flow filtration device. The results are shown in Table 2.

[0057] Table 2 Permeation flux of each nanofiltration membrane for different solutions

[0058] It can be seen from the above table: The flux of the nanofiltration membrane prepared in Examples 1-6 for ethanol is 106.55~242.11 L·h -1 m -2 , the flux of acetone is 45.69~93.8 L·h -1 m -2, the flux of dimethylformamide is 78.98~155.6 L·h -1 m -2 , the flux for n-hexane is 3.12~11.2 L·h -1 m -2 The nanofiltration membranes prepared in Examples 1-6 have high fluxes for solvents in different systems. Among them, by comparison, it can be seen that the permeation flux first increases and then decreases with the increase of the PDA-ZIF-8 nanoparticle dosage, and the permeation flux is the largest when the dosage is 0.012 wt%.

[0059] By comparing with Comparative Example 1, it was found that after adding PDA-ZIF-8 nanoparticles, the permeation flux of the composite membrane to the non-polar solvent n-hexane was significantly improved.

[0060] By comparing with Comparative Example 2, it is found that the composite membrane using the sulfonated polyetheretherketone as the base membrane has better tolerance.

[0061] Furthermore, in order to understand the stability of each nanofiltration membrane, the following tests were also conducted: The nanofiltration membranes prepared in Example 1 and Comparative Example 2 were immersed in ethanol, acetone and n-hexane solvents at 25°C for 14 days, and in phosphoric acid and dimethylformamide at 80°C for 14 days, respectively, to observe whether delamination or peeling occurred. The results are shown in Table 3.

[0062] Table 3 The results of nanofiltration membranes soaked for 14 days under different conditions

[0063] It can be seen from the above table: The nanofiltration membrane prepared in this example has good stability. It remains intact after being immersed in different solvents at room temperature (25°C) for 14 days, and its service life is guaranteed. It also remains intact after being immersed in different solvents at high temperature (80°C) for 14 days. However, the nanofiltration membrane in Comparative Example 2 can only remain intact at room temperature, and cannot meet the requirements for high-temperature operation scenarios.

[0064] From the above tests, it can be seen that the nanofiltration membrane prepared by the present invention has good separation performance, is suitable for different solution systems, and can maintain efficient retention for small molecular weight organic matter; at the same time, the stability of the nanofiltration membrane is also guaranteed, and it can adapt to higher temperature operating scenarios, and the scope of application is further expanded.

[0065] The specific raw materials not described in the present invention are all existing materials and can be directly purchased from the market.

[0066] The above are only preferred embodiments of the present invention and are not intended to limit the protection scope of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A composite layer polyetheretherketone organic solvent nanofiltration membrane, characterized in that: The nanofiltration membrane comprises a support layer and a selective separation layer; the support layer is a sulfonated polyetheretherketone based membrane, and the selective separation layer is a polyamide film formed by polymerization of piperazine monomers, PDA-ZIF-8 nanoparticles, and acyl chloride monomers at the interface of the support layer; Wherein, the PDA-ZIF-8 nanoparticles are prepared by the following method: S11, preparing a zinc nitrate hexahydrate-methanol solution and a 2-methylimidazole-methanol solution, mixing, stirring for reaction, centrifuging, removing the supernatant, washing with methanol, and vacuum drying to obtain ZIF-8 nanosheets; S12. Disperse ZIF-8 nanosheets in methanol, add Tris buffer and dopamine hydrochloride, stir to react, centrifuge, remove the supernatant and wash with methanol, and vacuum dry to obtain PDA-ZIF-8 nanoparticles.

2. The nanofiltration membrane according to claim 1, characterized in that In step S11, the molar ratio of zinc nitrate hexahydrate to 2-methylimidazole is 1:(5-10), the reaction is carried out for 0.5-4 hours, the centrifugal speed is 6000-12000 rpm, the methanol washing is repeated 2-5 times, and the vacuum drying temperature is 40-70°C.

3. The nanofiltration membrane according to claim 1, characterized in that In step S12, the mass ratio of ZIF-8 nanosheets to dopamine hydrochloride is (5-20):1, the concentration of Tris buffer is 10-30 mM, the reaction is performed for 4-6 hours, the centrifugal speed is 6000-12000 rpm, the methanol washing is repeated 2-5 times, and the vacuum drying temperature is 40-70°C.

4. The nanofiltration membrane according to any one of claims 1 to 3, characterized in that The piperazine monomers include hexahydropyrazine, N-methylpiperazine, and N-ethylpiperazine; The acyl chloride monomer includes trimesoyl chloride.

5. A method for preparing the nanofiltration membrane according to any one of claims 1 to 4, characterized in that: The following steps are involved: S21, dissolving polyetheretherketone in a mixed solution of methanesulfonic acid and sulfuric acid, stirring, and standing to remove bubbles to obtain a casting solution; coating the casting solution on a non-woven fabric support, standing, and immersing it in a deionized water precipitation bath to phase transform into a membrane, and washing the membrane to obtain a sulfonated polyetheretherketone base membrane; S22, dispersing PDA-ZIF-8 nanoparticles in a piperazine monomer solution to prepare an aqueous phase solution, and dissolving an acyl chloride monomer in a normal hexane solution to prepare an organic phase solution; S23, pouring the aqueous solution in step S22 onto the surface of the base membrane and letting it stand, and removing the excess aqueous solution on the membrane surface with a rubber roller; then slowly pouring the organic solution in step S22 onto the membrane surface, reacting, drying, and baking to obtain a nanofiltration membrane.

6. The preparation method according to claim 5, characterized in that: In step S21, the content of polyetheretherketone in the sulfonated polyetheretherketone base film is 5-20wt%; the molar ratio of methanesulfonic acid to sulfuric acid is (1-5):

1.

7. The preparation method according to claim 5, characterized in that: In step S22, the concentration of piperazine monomers in the aqueous solution is 0.0025-1.5 wt %; the concentration of PDA-ZIF-8 nanoparticles in the aqueous solution is 0.001-0.02 wt %.

8. The preparation method according to claim 5, characterized in that: The concentration of the acyl chloride monomer in the organic phase solution in step S22 is 0.001-1.0 wt %.

9. The preparation method according to claim 5, characterized in that: In step S23, the aqueous solution is allowed to stand on the base film for 0.5 to 5 minutes, and the organic solution is allowed to react on the base film for 0.5 to 2 minutes; the baking conditions are: 40 to 70° C., 5 to 30 minutes.

10. Use of the nanofiltration membrane according to any one of claims 1 to 4 in separation of an organic solution system.

Citation Information

Patent Citations

  • Method for preparing sulfonated polymer films

    CN101531765A

  • Preparation method of metal organic frame ZIF-8 / polydopamine hybrid molecular sieve gas separation membrane

    CN106000132A

  • MOF (metal organic framework) modified nanofiltration / reverse osmosis membrane and application thereof

    CN109224861A

  • Preparing method of zinc-coordination organic nano particle hybridization polyamide membrane

    CN109603563A

  • Dopamine-assisted modified hybrid composite forward osmosis membrane and preparation method thereof

    CN111001318A

Cited By

  • High-flux high-pollution-resistance nanofiltration membrane as well as preparation method and application thereof

    CN121911241A